Domains associated with successful quality improvement in healthcare - a nationwide case study - Aleidis Skard Brandrud; Bjørnar Nyen; Per Hjortdahl; Leiv Sandvik; Gro Sævil Helljesen Haldorsen; Maria Bergli; Eugene C. Nelson; Michael Bretthauer (BMC, 2017)
Abstract Background There is a distinct difference between what we know and what we do in healthcare: a gap that is impairing the quality of the care and increasing the costs. Quality improvement efforts have been made worldwide by learning collaboratives, based on recognized continual improvement theory with limited scientific evidence. The present study of 132 quality improvement projects in Norway explores the conditions for improvement from the perspectives of the frontline healthcare professionals, and evaluates the effectiveness of the continual improvement method. Methods An instrument with 25 questions was developed on prior focus group interviews with improvement project members who identified features that may promote or inhibit improvement. The questionnaire was sent to 189 improvement projects initiated by the Norwegian Medical Association, and responded by 70% (132) of the improvement teams. A sub study of their final reports by a validated instrument, made us able to identify the successful projects and compare their assessments with the assessments of the other projects. A factor analysis with Varimax rotation of the 25 questions identified five domains. A multivariate regression analysis was used to evaluate the association with successful quality improvements. Results Two of the five domains were associated with success: Measurement and Guidance (p = 0.011), and Professional environment (p = 0.015). The organizational leadership domain was not associated with successful quality improvements (p = 0.26). Conclusion Our findings suggest that quality improvement projects with good guidance and focus on measurement for improvement have increased likelihood of success. The variables in these two domains are aligned with improvement theory and confirm the effectiveness of the continual improvement method provided by the learning collaborative. High performing professional environments successfully engaged in patient-centered quality improvement if they had access to: (a) knowledge of best practice provided by professional subject matter experts, (b) knowledge of current practice provided by simple measurement methods, assisted by (c) improvement knowledge experts who provided useful guidance on measurement, and made the team able to organize the improvement efforts well in spite of the difficult resource situation (time and personnel). Our findings may be used by healthcare organizations to develop effective infrastructure to support improvement and to create the conditions for making quality and safety improvement a part of everyone's job.